2014
DOI: 10.4062/biomolther.2013.106
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and Apoptosis Induction Effects of Paeonol on Mice Bearing EMT6 Breast Carcinoma

Abstract: Paeonol is a major phenolic micromolecular component of Moutan cortex Radicis, a traditional Chinese Medicine. It has shown antitumor effects in previous studies; however, the underlying mechanisms remain unknown. This study investigated the mechanism by giving treatments of placebo, cyclophosphamide, paeonol of 150 and 300 mg/kg to 4 groups of mice bearing EMT6 breast cancer. Apoptosis in tumor cells were confirmed by morphology analysis, including hematoxylin, eosin staining and TUNEL staining. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…Previous studies have demonstrated that the mechanism of Pae's antitumor effect is via induction of apoptosis, stimulation of IL-2, and TNF-α production. 5,12,35 In the current study, we showed that Pae-induced apoptosis is closely related to the induction of ROS and the suppression of Akt activation in human lung cancer cells. Furthermore, drug-loaded nanoparticles exhibit clear A similar study is ongoing in the authors' laboratory, focusing on the synergistic effect and the underlying mechanisms of Pae and paclitaxel in several cancer cell lines.…”
Section: Modulation Of Akt/apoptotic Pathways By Pae-npsmentioning
confidence: 50%
“…Previous studies have demonstrated that the mechanism of Pae's antitumor effect is via induction of apoptosis, stimulation of IL-2, and TNF-α production. 5,12,35 In the current study, we showed that Pae-induced apoptosis is closely related to the induction of ROS and the suppression of Akt activation in human lung cancer cells. Furthermore, drug-loaded nanoparticles exhibit clear A similar study is ongoing in the authors' laboratory, focusing on the synergistic effect and the underlying mechanisms of Pae and paclitaxel in several cancer cell lines.…”
Section: Modulation Of Akt/apoptotic Pathways By Pae-npsmentioning
confidence: 50%
“…[9][10][11] Previous studies suggested that Paeonol possesses anti-proliferation, apoptosis induction, and cell cycle arresting effects in various types of cancers, such as breast, colorectal, lung, ovarian, gastric cancer, etc. 9,[12][13][14][15][16][17][18][19][20][21] More recent studies reported that Paeonol enhanced paclitaxel-induced apoptosis in breast cancer cells, 20,22 reversed Doxorubicin resistance in liver cancer, 23 and enhanced the radiosensitivity of lung cancer cells. 24 Studies also reported the anti-metastatic activities of Paeonol in human fibrosarcoma, chondrosarcoma and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike cytotoxic drugs, paeonol has shown cardioprotective, 16 hepatic-protective, 17−19 renal protective 20 and neuroprotective effects. 21 Paeonol has been shown to exhibit antitumor activities on gastric, 22,23 prostate, 24 breast, 25 hepar, 26 ovarian 27 and esophageal cancer cells. 28 Our previous study also revealed that paeonol exhibited the inhibiting effects on colorectal cancer lines (HCT116, SW620 and LoVo), especially in the LoVo cells.…”
Section: Introductionmentioning
confidence: 99%